The Development of Macroprudential Regulation of Bank Household Lending in Russia - O. S. Miroshnichenko; N. S. Voronova; V. V. Gamukin (Финансы: теория и практика, 2020)
The article highlights the use of macroprudential instruments by the Bank of Russia that regulate the population Lending of the Russian banking sector. The purpose of the work is to study the theoretical background and practical results of using indicators of the total cost of credit and the debt load of the population to ensure stability of the banking sector. The authors used methods of qualitative and quantitative analysis of scientific publications, regulatory sources, retrospective statistics. The study showed that initially, the regulator introduces new macroprudential instruments as recommended, and subsequently transfers them to mandatory. The regulatory mechanism is based on the ratio dependence of the bank capital adequacy on the actual values of the total loan cost and debt load of the borrower - individual. The mortgage debt to collateral value ratio supports the housing mortgage lending regulation process. The authors concluded that the banking sector’s reaction to the introduction of the total credit cost indicator is more prominent than the introduction of the debt burden indicator. When the Bank of Russia obliged to take into account the full cost of the loan when measuring capital adequacy, banks were not able to increase capital; they reduced high-risk lending. The practice of macroprudential regulation of credit risks in the banking sector is complemented by the introduction of credit holidays for borrowers - individuals, who are struggling because of the pandemic. The obtained theoretical and practical results can be used in the development of the financial stability regulation practice in Russia, at the micro-level - when designing and changing credit policy.